VERBAL AND VISUAL CONTENT OF CONTEMPORARY UKRAINIAN ONLINE COMICS - Nesterenko, Olesia (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. The relevance of the article is determined by the need to investigate the verbal and visual content of modern Ukrainian online comics. Analysis of content and visual elements of graphic stories published on virtual platforms is important for determining the structure of materials and establishing effective communication with readers. Purpose. The purpose of the article is to research the verbal and visual content of Ukrainian online comics, to single out the main thematic areas that attract the reader’s attention, and to analyze the influence of this genre on modern society. Methods. The main methods of research are the methods of analysis and synthesis – to clarify the state of research of the problem and the prospects for its solution; comparison – to analyze the views of scientists on the problem raised; descriptive method – to systematize the content and visual content of online comics; generalization – to develop a general research strategy and formulate conclusions. Results. Based on the analysis, it was established that the thematic orientation of Ukrainian online comics is diverse. They cover various spheres of life – from common realities to the depiction of fantastic and mystical worlds, which makes it possible to satisfy the interests of different groups of readers and maintain their interest in graphic stories. The study of the verbal and visual content of the Ukrainian comics published in the journal of social comics “Inker” testified to the actualization of the topic of the Russian-Ukrainian war, as well as the significance of the problem of stigmatization of victims of sexual violence, etc. The theme of the war is represented, in particular, by reports about the first weeks of the full-scale invasion, stories about Ukrainian women who went to fight, a story about two lovers who stood up for the defense of the country, and stories about the activities of partisans in the occupied territories, etc. The trademark features of the comics are outlined: the use of pictorial elements, the involvement of dialogues and monologues of the characters to tell the story; the use of artistic tropes and means of humor to attract the attention of readers; the use of frames, panels and “word bubbles” to organize the text and its logical structuring. Originality. The originality of the scientific research lies in the fact that the expediency of using the term “malopys” in the Ukrainian online space to denote a graphic-narrative art form, a series of drawings with short texts that form a coherent narrative, is motivated. The groundlessness of using the concept of “comics” in relation to modern Ukrainian illustrated stories has been proven, given their social orientation and often dramatic or tragic plot. Conclusion. It was concluded that the synthesis of verbal and visual components contributes to a more effective reproduction of emotions, feelings and facial expressions of the characters, testifying to the productivity of comics as media messages, which are characterized by exciting content and plot intrigue. It is noted that the social problems highlighted in the comics stimulate readers to take an active part in solving them, and therefore comic culture serves as an important element of the development of modern culture in general.